E-011 Wingspan stent for symptomatic intracranial stenosis: a single center analysis. (4th July 2012) - Baxter, B; Quarfordt, S; Hungerford, J; Kline, A; Maass, G; Huang, X
Abstract : Background: The role of Wingspan stent placement for the treatment of symptomatic intracranial stenosis has been greatly questioned in the wake of the SAMMPRIS trial results, which found a disparity between its treatment arms of medical management with Wingspan stenting and medical management alone for stroke or death at 30 days. The 30-day and 1-year probabilities of the primary endpoint of the SAMMPRIS trial (any stroke or death within 30 days or ischemic stroke in the territory of the qualifying artery beyond 30 days) were 5.8% and 12.2% for the medical management arm and 14.7% and 20.0% for the Wingspan arm, respectively. Purpose: The purpose of this real world study was to evaluate patient outcomes at Erlanger Medical Center who received a Wingspan stent and compare to the SAMMPRIS trial results. Methods: This was a retrospective cohort analysis of Wingspan stent use for symptomatic intracranial stenosis of a major cerebral artery and compared single center Wingspan group outcomes to those reported for medical management alone from the multi-center SAMMPRIS trial. Consistent with SAMMPRIS, the primary endpoint was any stroke or death within 30 days, or ischemic stroke in the territory of the qualifying artery beyond 30 days. Results: With a mean follow-up period of 2.1 years, the 30-day and 1-year probabilities of the primary endpoint were both 10.4% (n=42). Patient characteristics associated with higher risks of adverse events included female sex, diabetes mellitus, location of stent placement, and severity of the offending stenosis. Conclusion: Outcomes after Wingspan stenting at this single medical center were only inferior to those from the SAMMPRIS medical management arm at 30 days, but not at 1 year. Outcomes at 30 days and 1 year were both lower than those reported from the SAMMPRIS Wingspan arm and seem to be more consistent with those previously published from other Wingspan registries. Unlike the SAMMPRIS trial results, there was no increase in the probability of the primary endpoint between 30 days and 1 year. This real world experience suggests that the role of Wingspan stenting needs further investigation, and continued evaluation of intracranial stenting for symptomatic intracranial stenosis seems worthwhile. Competing interests: B Baxter: Stryker Neurovascular, Penumbra, Codman, EV3, Rapid Medical, Reverse Medical. S Quarfordt: None. J Hungerford: None. A Kline: None. G Maass: None. X Huang: None.